2022
DOI: 10.21018/rjcpr.2022.2.342
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of Communication Freelancers and Online Communities. A Mixed Methods Approach

Abstract: The present study explores the nature and dynamics of online communities populated by communication freelancers. Drawing from limited scholarship focusing on freelance work practices in communication industries and a reduced number of studies in communication literature regarding online communities, this research applies a complex analytical framework, with mixed methodology: content analysis, social network analysis and thematic analysis. Our main findings reveal the key features of the discursive environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…That is, successes in previous behavior increase self-efficacy, while experienced failures may decrease self-efficacy, which in turn supports users in deciding whether to reinforce or reduce the behavior [69]. Moise and Anton [70] argued that sharing knowledge with others increases user self-efficacy. Smirnova, Reitzig [54] also found that by sharing useful knowledge with others in an online community, participants would gain more confidence in their achievements.…”
Section: Reinforcement Learning and Self-efficacymentioning
confidence: 99%
“…That is, successes in previous behavior increase self-efficacy, while experienced failures may decrease self-efficacy, which in turn supports users in deciding whether to reinforce or reduce the behavior [69]. Moise and Anton [70] argued that sharing knowledge with others increases user self-efficacy. Smirnova, Reitzig [54] also found that by sharing useful knowledge with others in an online community, participants would gain more confidence in their achievements.…”
Section: Reinforcement Learning and Self-efficacymentioning
confidence: 99%